1998
DOI: 10.1292/jvms.60.513
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Orotic-Acid-Induced Fatty Liver in Male Rats by Dehydroepiandrosterone and/or Phenobarbital.

Abstract: ABSTRACT. Dehydroepiandrosterone (DHEA) is a steroid hormone which induces the peroxisome proliferation in rodents. The fatty liver induced by orotic acid and a high sucrose diet in male rats was prevented by the administration of DHEA and/or phenobarbital (PB). A significant increase in the liver weight was induced in the DHEA group (relative weight) and the DHEA + PB group (absolute and relative weight). The liver weight increased more conspicuously in the DHEA + PB group than in the DHEA group. The increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In addition, the TG accumulation induced by orotic acid is facilitated by a high-sucrose diet (Novikoff et al, 1974). Our early studies reproduced the marked accumulation of lipid droplets in hepatocytes using a combination of treatments with orotic acid and sucrose (Goto et al, 1998a(Goto et al, , 1998b). These observations were also supported by those from the present study.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In addition, the TG accumulation induced by orotic acid is facilitated by a high-sucrose diet (Novikoff et al, 1974). Our early studies reproduced the marked accumulation of lipid droplets in hepatocytes using a combination of treatments with orotic acid and sucrose (Goto et al, 1998a(Goto et al, , 1998b). These observations were also supported by those from the present study.…”
Section: Discussionsupporting
confidence: 60%
“…A previous study has already revealed that unconjugated DHEA, PB or a combination of the two prevents orotic acid-induced fatty liver in male rats (Goto et al, 1998a). The preventive effect of DHEA acetate has also been reported (Goto et al, 1998b).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…From this perspective, we examined the effect of some compounds on fatty liver improvement by using NAFL model rats induced by orotic acid with a highsucrose diet, in which the disease level of fatty liver is relatively mild. Our previous research showed that some compounds alleviated fatty liver following the administration of the peroxisome proliferator dehydroepiandrosterone sulfate (DHEAS) and/or the administration of the cytochrome P450 (CYP) inducer phenobarbital (PB) to NAFL model rats induced by orotic acid with a highsucrose diet (Goto et al, 1998a(Goto et al, , 1998bTakeuchi et al, 2015). The lipid droplets were significantly reduced from the fatty liver as a consequence of enhancing the metabolic reaction (Goto et al, 1998a(Goto et al, , 1998bTakeuchi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…8) Furthermore, it has been reported that increased triglyceride synthesis mediated by changes in liver phosphatidate phosphohydrolase activity was involved in the hepatic triglyceride accumulation induced by orotic acid administration and that this change was markedly suppressed by dietary n-3 fatty acids. 9) Goto et al 10) also have been reported that dehydroepiandrosterone, as well as cloˆbrate, may prevent orotic-acid-induced fatty liver.…”
mentioning
confidence: 96%